2014
DOI: 10.1007/s10886-014-0505-2
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress and Leaf Herbivory Affect Root Terpenoid Concentrations and Growth of Tanacetum vulgare

Abstract: Plant responses of both shoots and roots to combined abiotic and biotic stress have been rarely investigated. However, stresses such as drought and aboveground herbivory might lead to conflicting resource allocation patterns and pronounced shifts in shoot vs. root defenses. In the present study, the effects of water availability and leaf herbivory by caterpillars of a generalist on various shoot and root traits of the aromatic plant Tanacetum vulgare L. were investigated. This species contains terpenoids in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 61 publications
3
34
1
Order By: Relevance
“…However, the combined effects of water stress and previous herbivory is often overlooked in studies that examine the effect of water stress on insect performance. Several studies have shown that water-stressed plants are better able to induce resistance traits and reduce insect performance compared with well-watered plants (Tariq et al, 2013;Kleine & Muller, 2014). Another study, however, showed that drought can inhibit the induction of resistance traits (Halpern et al, 2010), while others found no or mixed effects of drought on inducibility (Hale et al, 2005;Gutbrodt et al, 2012;Weldegergis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the combined effects of water stress and previous herbivory is often overlooked in studies that examine the effect of water stress on insect performance. Several studies have shown that water-stressed plants are better able to induce resistance traits and reduce insect performance compared with well-watered plants (Tariq et al, 2013;Kleine & Muller, 2014). Another study, however, showed that drought can inhibit the induction of resistance traits (Halpern et al, 2010), while others found no or mixed effects of drought on inducibility (Hale et al, 2005;Gutbrodt et al, 2012;Weldegergis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Cymbopogon winterianus (citronella), whose leaves are known to have antimicrobial properties, shows higher expression of terpenoid biosynthesis genes in leaves compared to roots [45]. Also, terpenoids accumulate in roots in response to drought in many plants, including Tanacetum vulgare (tansy) and maize [46,47]. Most likely these compounds act as antioxidants to protect plants against oxidative stress caused by drought.…”
Section: Upregulation Of Genes Involved In Terpenoid Biosynthesis In mentioning
confidence: 99%
“…Terpenoids in plant shoots decreased after 12 days of moderate drought exposure in contrast to increasing accumulation in plant roots, suggesting increased root protection against soil insects and pathogens. In this case, belowground plant organs may impact the systemic defense system deployed by T. vulgare through the reallocation of resources critical for regeneration following exposure to stress …”
Section: Introductionmentioning
confidence: 99%
“…2,16,17 Drought stress in plants can result in accumulation of ROS, 2 and bioaccumulation of bioactive terpenes, terpenoids, phenols and alkaloids in multiple herbaceous and woody species that facilitate defense against insects, pathogens and weeds. 17,18 Many of these metabolites play important ecological or defensive roles against pests following exposure to stress. Terpenoids, for example, play a vital role in plant defense as phytoalexins and also as attractants to insect pollinators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation